2018
DOI: 10.1038/s41598-018-27610-y
|View full text |Cite
|
Sign up to set email alerts
|

A pivotal role for starch in the reconfiguration of 14C-partitioning and allocation in Arabidopsis thaliana under short-term abiotic stress

Abstract: Plant carbon status is optimized for normal growth but is affected by abiotic stress. Here, we used 14C-labeling to provide the first holistic picture of carbon use changes during short-term osmotic, salinity, and cold stress in Arabidopsis thaliana. This could inform on the early mechanisms plants use to survive adverse environment, which is important for efficient agricultural production. We found that carbon allocation from source to sinks, and partitioning into major metabolite pools in the source leaf, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 73 publications
1
38
0
Order By: Relevance
“…Previous studies in Arabidopsis showed that 150 mM salt stress results in increased sugar accumulation and reduced starch content [51], highlighting that STY46, is necessary for this physiological process. Our work suggests the activation of a regulatory mechanism, whereby carbon is preferentially partitioned into osmoprotectants (sugars, amino acids, organic acids) at the expense of storage compounds (starch or protein) as a positive way to respond to salinity stress [34]. The 14 CO 2 labeling experiment reinforced this and showed that OE-25 partitioned more 14 C into amino acids (AA) and sugars, while it partitioned less into starch and protein in source leaf, which suggested that OE-25 is more responsive to salinity stress than the wild type.…”
Section: The Role Of Sty46 In Abiotic Stress Responsementioning
confidence: 96%
See 4 more Smart Citations
“…Previous studies in Arabidopsis showed that 150 mM salt stress results in increased sugar accumulation and reduced starch content [51], highlighting that STY46, is necessary for this physiological process. Our work suggests the activation of a regulatory mechanism, whereby carbon is preferentially partitioned into osmoprotectants (sugars, amino acids, organic acids) at the expense of storage compounds (starch or protein) as a positive way to respond to salinity stress [34]. The 14 CO 2 labeling experiment reinforced this and showed that OE-25 partitioned more 14 C into amino acids (AA) and sugars, while it partitioned less into starch and protein in source leaf, which suggested that OE-25 is more responsive to salinity stress than the wild type.…”
Section: The Role Of Sty46 In Abiotic Stress Responsementioning
confidence: 96%
“…The idea that STY46 may be part of a biological pathway integrating carbon availability and abiotic stress was directly tested. The STY46 genotypes were exposed to 150 mM mannitol and 100 mM NaCl stress, and carbohydrates were assayed in rosettes and harvested at the end of the light period, when carbohydrate content was highest [34]. There were no differences in starch and reducing sugar contents among genotypes under non-stressed conditions ( Figure 6B,C).…”
Section: Characterization Of Sty46 Transgenic Plants Under Stressmentioning
confidence: 96%
See 3 more Smart Citations